Neurosurgical aspects of abusive head trauma management in children: a review for the training neurosurgeon. (2nd January 2019) - Fitzpatrick, S.; Leach, P.
Abstract: The management of head trauma in children from suspected abuse is multidisciplinary. The primary role of neurosurgeons is to manage the acute clinical situation. They also have a secondary role in assisting others to determine the cause of the injury and prevent recurrences. This article aims to guide the trainee neurosurgeon on management of this patient group according to current literature.